Aprendizaje y Práctica en la Patología Músculo Esquelética Arpeo Idiopático en Caballos Criollos Colombiano (2023)
The study focused on the comprehensive analysis of grappling, an abnormality that affects the Functionality of the hind limbs in horses of the Colombian Creole breed. The objective The main objective was to examine the incidence of this pathology, as well as its consequent impact on the mobility and quality of life of affected horses. Both the idiopathic arpeo, whose origin is not identified, such as acquired hooking, associated with the ingestion of phytotoxic agents, are the subject of investigation.